Evaluation method for low-temperature crystallization of vulcanized rubber

The lateral radiation time of silicone is measured by pulsed NMR technology, combined with cooling and storage steps, the T2 value change rate is calculated to evaluate the low-temperature crystallization properties of silicone, solving the problem that the existing technology is difficult to evaluate the low-temperature crystallization properties of silicone, and achieving efficient and accurate evaluation of different silicone.

JP7659266B2Active Publication Date: 2025-04-09HIROSHIMA UNIVERSITY +2
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021129935
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-06
Publication Date
2025-04-09
Estimated Expiration
2041-08-06

AI Technical Summary

Technical Problem

The prior art is difficult to effectively evaluate and distinguish the crystallization properties of different types of silica gels in low temperature environments, especially in extremely low temperature environments (such as -100°C or below), and traditional methods cannot accurately reflect the crystallization behavior of natural rubber at low temperatures.

Method used

The low-temperature crystallization properties of silica gel were evaluated by measuring the transverse radiation time (T2) at different temperatures and combined with solid echo method. The specific steps include: first measuring the T2 value of the silicone at room temperature, then cooling the silicone to a certain temperature (Tc) and storing it for a certain period of time to promote crystallization, and then performing a second measurement to obtain the crystallized T2 value, and calculating the change rate of the T2 value (ΔT2) as an evaluation index.

Benefits of technology

This method can easily and reliably evaluate the crystallization properties of silicone in extremely low temperature environments, avoid the high cost of sample shape and cooling equipment in traditional methods, and can effectively distinguish the low-temperature crystallization behavior of different silicone, and is suitable for various silicone compositions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659266000006
    Figure 0007659266000006
  • Figure 0007659266000007
    Figure 0007659266000007
  • Figure 0007659266000008
    Figure 0007659266000008
Patent Text Reader

Abstract

To provide a simple and reliable method for evaluating the crystalline nature of a vulcanized rubber which progresses under exposure to a low-temperature environment for a long time.SOLUTION: The method includes: a first measurement step S1 for deriving the motility of a vulcanized rubber in an uncrystallized melting state from a transverse relaxation time (T2) measured by using a solid echo technique of a pulse NMR; a crystallization step S2 for cooling the vulcanized rubber to a predetermined temperature (Tc) at which the vulcanized rubber can be crystallized and storing the rubber at the predetermined temperature (Tc) for a certain time to make the crystallization of the vulcanized rubber progress; a second measurement step S3 for deriving the motility of the vulcanized rubber crystallized in the crystallization step from the transverse relaxation time (T2) measured by using the solid echo technique of the pulse NMR; and an evaluation step S4 for calculating a rate of change (ΔT2) of the transverse relaxation time from the transverse relaxation time in the first measurement step and in the second measurement step and evaluating the crystalline nature of the vulcanized rubber with the rate of change as an evaluation index.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for evaluating the low-temperature crystallinity of vulcanized rubber. [Background technology]

[0002] 2. Description of the Related Art Elastic vulcanized rubber is widely used in various fields, for example, in vehicles such as automobiles, for use as vibration-proof members that elastically support supported components such as engines and transmissions on the vehicle body, and in tires.

[0003] It is known that such vulcanized rubber loses elasticity in a low-temperature environment. In recent years, problems have arisen in which products made of vulcanized rubber lose their functionality when exposed to a low-temperature environment. This is thought to be caused by crystallization of the vulcanized rubber. In light of this situation, there is a demand for vulcanized rubber that is less likely to crystallize even when exposed to a low-temperature environment.

[0004] Incidentally, natural rubber, which is the raw material for vulcanized rubber, is known to exhibit at least two types of crystallization phenomena. These are self-reinforcing template crystallization and low-temperature crystallization. Natural rubber exhibits unique crystallization behavior among polymers, and it is particularly difficult to grasp the behavior of low-temperature crystallization. The generation of crystal nuclei in natural rubber depends on fluctuations in density and micro-Brownian motion, so it is considered difficult to control crystallization in practice. (Non-Patent Documents 1-3) As a test method for evaluating the characteristics of vulcanized rubber, Patent Document 1 describes a method for predicting the physical properties of rubber using a pulsed NMR device.

[0005] A conventional test method for evaluating the properties of vulcanized rubber at low temperatures is to install a refrigerator in a static and dynamic spring property tester and measure the spring constant in a low-temperature environment. Patent Document 2 describes evaluating the low-temperature crystallization of a rubber composition using the melting enthalpy obtained by a general measurement method of DSC. Patent Document 3 describes measuring the temperature dispersion curve of the viscoelasticity of a vulcanized rubber composition, and determining the presence or absence of a peak derived from low-temperature crystallization of the rubber material from the obtained tan δ curve. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] "Rubber Science - Its Modern Approach" by Yuko Ikeda et al., Asakura Publishing [Non-Patent Document 2] ▲Koji▼Shinzo Tani et al., "Rubber Reinforcement -Mechanism Analysis by Visualization of Nanofillers", Asakura Publishing [Non-Patent Document 3] Edited by the Society of Polymer Science, "Basic Polymer Science", Tokyo Kagaku Doujin Publishing [Patent documents]

[0007] [Patent Document 1] JP 2020-085777 A [Patent Document 2] Patent No. 6806786 [Patent Document 3] Patent No. 6141118 Summary of the Invention [Problem to be solved by the invention]

[0008] The evaluation method of Patent Document 1 evaluates the thermal degradation of rubber, but does not evaluate the properties of rubber that has been exposed to low temperatures and undergoes crystallization. It can be said that no method has been established to evaluate the low-temperature crystallization of vulcanized rubber using pulse NMR.

[0009] Evaluation using a spring property tester is not suitable for evaluating the low-temperature crystallization of vulcanized rubber because it requires test pieces of a specific shape, and it is very costly to install a refrigerator in the static and dynamic spring property tester. Furthermore, there is a limit to the cooling performance of low-temperature equipment such as refrigerators that can be installed in static and dynamic spring property testers, making it impossible to evaluate at extremely low temperatures, for example, below -100°C.

[0010] The evaluation methods described in Patent Documents 2 and 3 predict the crystallinity of a rubber composition by measuring the properties of the rubber composition when it is momentarily exposed to low temperatures. The crystallization of vulcanized rubber progresses gradually over time, and as described above, it is difficult to grasp the behavior of low-temperature crystallization, but these methods do not take into account the low-temperature crystallization characteristic of natural rubber. Therefore, when using these methods to evaluate, for example, a rubber material with a relatively slow crystallization rate, there are problems in that no significant difference is observed between multiple vulcanized rubbers, and the evaluation results may not correspond to the actual low-temperature crystallization.

[0011] The technology disclosed in this specification has been made in consideration of the above points, and its objective is to provide a simple and reliable method for evaluating the low-temperature crystallization of vulcanized rubber that progresses after being exposed to a low-temperature environment for a long period of time. [Means for solving the problem]

[0012] The technology disclosed in this specification is A method for evaluating low-temperature crystallinity of vulcanized rubber using pulsed NMR, comprising: A first measurement step of deriving the mobility of the vulcanized rubber in a non-crystallized molten state from the transverse relaxation time (T2) measured using the solid echo method of pulsed NMR; a crystallization step of cooling the vulcanized rubber to a predetermined temperature (Tc) at which the vulcanized rubber can be crystallized and storing the vulcanized rubber at the predetermined temperature (Tc) for a certain period of time to promote crystallization of the vulcanized rubber; A second measurement step of deriving the mobility of the vulcanized rubber crystallized in the crystallization step from a transverse relaxation time (T2) measured using a solid echo method of pulsed NMR; From the measured transverse relaxation time (T2) in the first measurement step and the measured transverse relaxation time (T2) in the second measurement step, the following formula (1) is calculated. {(transverse relaxation time (T2) in the second measurement step / transverse relaxation time (T2) in the first measurement step)-1}×100 … Equation (1) and an evaluation step of calculating a rate of change (ΔT2) in the transverse relaxation time by the above-mentioned method, and evaluating the crystallinity of the vulcanized rubber using the rate of change (ΔT2) as an evaluation index.

[0013] According to this, by using pulse NMR, it is not necessary to prepare samples of a predetermined shape, as in the case of a spring property tester, and it is easy to evaluate various vulcanized rubbers even with a small amount of samples, regardless of the shape. In addition, it is possible to grasp the molecular mobility of vulcanized rubber from the relaxation time obtained by pulse NMR measurement. It is possible to grasp the change in mobility due to the progress of crystallization by calculating the change rate of the transverse relaxation time from the measurement result of vulcanized rubber in a molten state that has not been crystallized and the measurement result of vulcanized rubber that has been exposed to a low temperature for a certain time to progress crystallization. Instead of measuring the instantaneous low-temperature properties of vulcanized rubber, by storing vulcanized rubber for a certain time at a predetermined temperature (Tc) at which vulcanized rubber can crystallize and progressing crystallization, it is possible to measure vulcanized rubber that is close to the state in which defects have actually been reported, and therefore it is highly reliable as a method for evaluating the low-temperature crystallization of vulcanized rubber. In addition, by using such a change rate as an evaluation index, it is possible to efficiently and appropriately evaluate vulcanized rubbers of various compositions.

[0014] The vulcanized rubber preferably includes natural rubber or isoprene rubber.

[0015] The predetermined temperature (Tc) is preferably a temperature that is 10°C to 40°C higher than the glass transition temperature (Tg) of natural rubber or isoprene rubber. The predetermined temperature (Tc) is preferably -60°C to -30°C.

[0016] It is generally said that the crystallization rate of vulcanized rubber is highest in a temperature range slightly higher than the glass transition temperature (Tg). The temperature range where the crystallization rate is highest varies depending on the rubber component, but in vulcanized rubber containing natural rubber or isoprene rubber, if the predetermined temperature (Tc) for promoting crystallization is set to a temperature 10°C to 40°C higher than the glass transition temperature (Tg) of natural rubber or isoprene rubber, it is possible to reliably promote the crystallization of the vulcanized rubber, and this method has excellent versatility as a method for evaluating the low-temperature crystallization of vulcanized rubber.

[0017] The pulse NMR measurements in the first and second measuring steps are preferably performed at a temperature higher than -60°C and lower than -20°C.

[0018] It is also preferable that the certain period of time is at least 24 hours. Effect of the Invention

[0019] As described above, the technology disclosed in this specification makes it possible to provide a simple and highly reliable method for evaluating the low-temperature crystallization of vulcanized rubber that progresses after being exposed to a low-temperature environment for a long period of time. [Brief description of the drawings]

[0020] [Figure 1] 1 is a flowchart showing an example of a method for evaluating low-temperature crystallinity of vulcanized rubber according to the present disclosure. [Diagram 2] 1 is a graph showing the correlation between relaxation time T2(1) and low-temperature storage time in measurements at −30° C. [Diagram 3] 1 is a graph showing the correlation between relaxation time T2(2) and low-temperature storage time in measurements at −30° C. [Figure 4] 1 is a graph showing the correlation between relaxation time T2(1) measured at −20° C. and low-temperature storage time. [Diagram 5] 1 is a graph showing the correlation between relaxation time T2(2) in measurements at −20° C. and low-temperature storage time. [Figure 6]1 is a graph showing the correlation between relaxation time T2(1) in measurements at −60° C. and low-temperature storage time. [Figure 7] 1 is a graph showing the correlation between relaxation time T2(2) in measurements at −60° C. and low-temperature storage time. [Figure 8] 1 is a graph showing the correlation between relaxation time T2 and low-temperature storage time in 0° C. measurement by the spin echo method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, the embodiments of the present disclosure will be described. The following description of the preferred embodiments is merely illustrative in nature and is not intended to limit the present disclosure, its application, or its uses.

[0022] The technology disclosed in this specification involves cooling vulcanized rubber to a predetermined temperature (Tc) at which the vulcanized rubber can crystallize, storing the vulcanized rubber at the predetermined temperature (Tc) for a certain period of time to allow crystallization to proceed, and deriving the mobility of the vulcanized rubber that has undergone crystallization by measuring the transverse relaxation time (T2) using pulse NMR. The rate of change (ΔT2) in the transverse relaxation time is calculated from the transverse relaxation time (T2) of the vulcanized rubber that has undergone crystallization and the transverse relaxation time (T2) of the vulcanized rubber in a molten state that has not been crystallized, and the rate of change is used as an evaluation index to evaluate the crystallinity of the vulcanized rubber.

[0023] [Vulcanized rubber] The vulcanized rubber to be evaluated is made by compounding a rubber component (polymer) with fillers and additives and then vulcanizing it.

[0024] The rubber component is not particularly limited, and may include, for example, natural rubber (NR) or isoprene rubber (IR). Natural rubber (NR) or isoprene rubber (IR) may be included alone, or natural rubber (NR) or isoprene rubber (IR) may be mixed with one or more other rubber components, such as butadiene rubber (BR), styrene butadiene rubber (SBR), butyl rubber (IIR), ethylene propylene rubber (EPDM), chloroprene rubber (CR), etc. The rubber components mixed with natural rubber (NR) or isoprene rubber (IR) are not limited to the above, and other rubber components may be used as long as they are capable of implementing the technology of the present disclosure. When a plurality of rubber components are mixed, the vulcanized rubber preferably contains 20% or more of natural rubber (NR) or isoprene rubber (IR) of the entire rubber components, and more preferably contains natural rubber (NR) or isoprene rubber (IR) as the main component. "Main component" means that among the multiple rubber components that make up the vulcanized rubber, natural rubber (NR) or isoprene rubber (IR) accounts for the largest proportion.

[0025] The filler may contain, for example, reinforcing fillers such as silica-based inorganic fillers such as SiO2, kaolin, talc, clay, mica, and diatomaceous earth, nanofillers such as cellulose nanofiber and graphite, and carbon black, non-reinforcing fillers such as metal oxides and metal hydroxides such as calcium carbonate, barium sulfate, and titanium oxide. By blending the reinforcing filler, the strength of the vulcanized rubber can be increased. In addition to the filler, vulcanization accelerators such as zinc oxide and stearic acid, antiaging agents, vulcanization accelerators, processing aids, softeners, and vulcanizing agents such as sulfur can be appropriately blended as compounding agents commonly used in the production of vulcanized rubber. The amount of each of these components to be blended is arbitrary.

[0026] Vulcanized rubber is obtained by kneading the materials in a mixer and vulcanizing them by heating, as is done in general rubber manufacturing.

[0027] [Low temperature crystallinity evaluation method] Using pulse NMR, the transverse relaxation time (T2) of the vulcanized rubber in a molten state that has not been crystallized and the transverse relaxation time (T2) of the vulcanized rubber that has been crystallized are measured, and the rate of change (ΔT2) of the transverse relaxation time is calculated, and the rate of change (ΔT2) is used as an evaluation index to evaluate the crystallinity of the vulcanized rubber. Specifically, crystallization, measurement, and evaluation are performed according to the procedure shown in Figure 1.

[0028] (1) First measurement step S1 In order to measure the mobility of vulcanized rubber in a molten state without crystallization, for example, vulcanized rubber that has been stored at room temperature after production and has not been exposed to a low-temperature environment is injected into an NMR tube, and the transverse relaxation time (T2) is measured at low temperature by the solid echo method of pulsed NMR. The measurement temperature of pulsed NMR is preferably higher than -60°C and lower than -20°C. The obtained decay curve is separated into two components, and the transverse relaxation time (T2) is measured by focusing on the component with high mobility. (2) )

[0029] (2) Crystallization step S2 The vulcanized rubber is cooled to a specified temperature (Tc) at which the vulcanized rubber can crystallize, and is stored at the specified temperature (Tc) for a certain period of time to promote crystallization of the vulcanized rubber.

[0030] The specified temperature (Tc) and storage time at which the vulcanized rubber can crystallize are arbitrary. For example, the specified temperature (Tc) and storage time may be determined to be conditions that reproduce the actual environment in which a decrease in functionality has been reported in parts in which vulcanized rubber is used.

[0031] A preferred predetermined temperature (Tc) is a temperature 10°C higher than the glass transition temperature (Tg) of natural rubber or isoprene rubber. In general, the glass transition temperature (Tg) of vulcanized rubber varies depending on the composition, manufacturing conditions, etc., and therefore has a temperature range. When the vulcanized rubber to be evaluated in the evaluation method of the present disclosure contains natural rubber or isoprene rubber, the vulcanized rubber is stored for a certain period of time at a predetermined temperature (Tc) that is 10°C to 40°C higher than the glass transition temperature (Tg) of natural rubber or isoprene rubber, whereby crystallization of the vulcanized rubber is promoted in this temperature range, and the evaluation of crystallinity can be facilitated. In general, the glass transition temperature (Tg) of natural rubber and isoprene rubber is known to be about -70°C to -50°C. A preferred predetermined temperature (Tc) for promoting crystallization is -60°C to -30°C.

[0032] The storage time at the above-mentioned specified temperature (Tc) is preferably at least 24 hours, and when evaluating a vulcanized rubber in which crystallization does not easily proceed, the storage time may be extended, for example, up to 72 hours.

[0033] (3) Second measurement process S3 The vulcanized rubber that has been crystallized in the crystallization step S2 is injected into an NMR tube, and low-temperature measurements are performed using the solid echo method of pulsed NMR. The mobility of the vulcanized rubber is evaluated based on the obtained transverse relaxation time (T2). The measurement temperature of the pulsed NMR is the same as that of the first measurement step S1, and is preferably higher than -60°C and lower than -20°C. The obtained decay curve is separated into two components, and the transverse relaxation time (T2) is calculated by focusing on the component with higher mobility. (2) )

[0034] (4) Evaluation process S4 From the measured transverse relaxation time (T2) in the first measurement step and the measured transverse relaxation time (T2) in the second measurement step, the rate of change in the transverse relaxation time is calculated by the following formula (1), and the crystallinity of the vulcanized rubber is evaluated using the rate of change as an evaluation index. {(transverse relaxation time (T2) in the second measurement step / transverse relaxation time (T2) in the first measurement step)-1}×100 … Equation (1) It is preferable that the measurement conditions of the pulsed NMR in the first measurement step S1 and the measurement conditions of the pulsed NMR in the second measurement step S3 are the same.

[0035] In a preferred embodiment, the decay curve obtained from pulsed NMR is separated into two components, and the transverse relaxation time (T2 (2) ), but focusing on the components with low mobility, the transverse relaxation time (T2 (1) ) and calculate the rate of change of the transverse relaxation time. EXAMPLES

[0036] [Composition of vulcanized rubber] Hereinafter, specific examples of the technology of the present disclosure will be described based on examples and comparative examples, but the technology of the present disclosure is not limited thereto.

[0037] Three types of vulcanized rubber, Compositions 1 to 3, evaluated under the measurement conditions of Example 1 and Comparative Examples 1 and 2 have the compositions shown in Table 1. The vulcanized rubbers of Compositions 1 to 3 contain 80 parts by weight of natural rubber (NR) and 20 parts by weight of butadiene rubber (BR) out of a total of 100 parts by weight of rubber components.

[0038] Compositions 1 to 3 have different crosslink densities due to the amount of sulfur added. Composition 1 is a vulcanized rubber with a medium crosslink density, composition 2 is a vulcanized rubber with a high crosslink density, and composition 3 is a vulcanized rubber with a low crosslink density.

[0039] [Table 1]

[0040] The types of raw materials used in Table 1 are shown below. Natural rubber (NR): RSS#3 Polybutadiene rubber (BR): Ubepol BR150 manufactured by Ube Industries Carbon black: Seast S manufactured by Tokai Carbon Co., Ltd. Zinc oxide: Two types of zinc oxide manufactured by Seido Chemical Industry Co., Ltd. Stearic acid: NOF Corp. bead stearic acid, Tsubaki Wax: Santite S manufactured by Seiko Chemical Co., Ltd. Anti-aging agent 1 (N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine): Nocrac 6C manufactured by Ouchi Shinko Chemical Co., Ltd. Anti-aging agent 2 (2-mercaptobenzimidazole): Nocrac MB manufactured by Ouchi Shinko Chemical Co., Ltd. Vulcanization accelerator 1 (N-oxydiethylene-2-benzothiazolylsulfenamide): Noccela MSA-G manufactured by Ouchi Shinko Chemical Co., Ltd. Vulcanization accelerator 2 (tetramethylthiuram disulfide): Noccela TT manufactured by Ouchi Shinko Chemical Co., Ltd. Sulfur: Finely powdered sulfur 325 mesh manufactured by Hosoi Chemical Industry Co., Ltd. [Production of vulcanized rubber] The vulcanized rubber can be produced by any method generally used for producing vulcanized rubber, but in this example, the vulcanized rubber was produced by the following method.

[0041] Compositions 1 to 3 were prepared by kneading materials other than sulfur and vulcanization accelerator using a Banbury mixer according to the composition shown in Table 1. Next, sulfur and vulcanization accelerator were added to the obtained mixture, and the mixture was kneaded using an open roll to obtain an unvulcanized rubber mixture. Furthermore, the obtained unvulcanized rubber mixture was poured into a 2 mm thick mold and press-vulcanized at 170°C for 5 minutes to obtain a vulcanized rubber.

[0042] The vulcanized rubber in a molten state that was not crystallized and used in the first measurement step S1 was stored at room temperature after production.

[0043] The vulcanized rubber used in the second measurement step S3 was stored in a freezer set at -60°C for a certain period of time to allow crystallization to proceed.

[0044] [Evaluation of low-temperature crystallization of vulcanized rubber] The transverse relaxation time T2 of the obtained vulcanized rubber was measured by pulse NMR.

[0045] The transverse relaxation time T2 reflects the molecular mobility of hydrogen atoms contained in vulcanized rubber. From the decay curve obtained by pulse NMR measurement, it is possible to separate components with low mobility and components with high mobility, and the transverse relaxation times of the components with low mobility and short relaxation times and the components with high mobility and long relaxation times are respectively T2 (1) ,T2 (2) Let us assume that.

[0046] Transverse relaxation time T2 (1) ,T2 (2) For each of them, the rate of change between the transverse relaxation time T2 of the vulcanized rubber in a molten state that has not been crystallized, measured in the first measurement step S1, and the transverse relaxation time T2 of the vulcanized rubber that has been allowed to undergo crystallization, measured in the second measurement step S3, is calculated, and the rate of change can be used as an index of crystallinity. The larger the rate of change, the higher the mobility of the rubber, and the easier it is to crystallize, and the smaller the rate of change, the lower the mobility of the rubber, and the harder it is to crystallize.

[0047] In addition, when calculating the rate of change in the transverse relaxation time T2, the component with low mobility and short relaxation time (T2 (1) ) or a highly mobile and long-relaxation component (T2 (2) ) or both may be used, but the component with high mobility and long relaxation time (T2 (2) ) has a lower kinetic and shorter relaxation time component (T2 (1) ), the components with high mobility and long relaxation times (T2 (2) ) is preferable.

[0048] Example 1 and Comparative Examples 1 and 2 will be further described below.

[0049] [Example 1] For the vulcanized rubbers of compositions 1 to 3, the transverse relaxation time (T2) of the vulcanized rubbers stored at room temperature was measured in the first measurement step S1. In addition, for each vulcanized rubber, in the crystallization step S2, after storing at -60°C for 0 hours, 24 hours, 48 ​​hours, 72 hours, and 168 hours, the transverse relaxation time (T2) was measured in the second measurement step S3. The measurement device and measurement conditions for pulse NMR are as follows. Equipment: Bruker, mq20 Sample volume: approx. 0.3 mL Observation kernel: 1 H Pulse sequence: Solid echo method Measurement temperature: -30℃ Initial data offset: 0 ms Final Pulse Separation: 2.0 ms Data point fitting:200 Scans:16 For each of the first and second measurement steps, the decay curves obtained at a measurement temperature of -30°C were separated into two components and analyzed. The two components are a component with low mobility and hardness (T2 (1) ) and highly mobile and soft components (T2 in Table 2) (2) ).

[0050] The transverse relaxation time (T (1) ,T2 (2) 2 and 3 are graphs in which the value of the temperature difference is plotted against the storage time (0 hours, 24 hours, 48 ​​hours, 72 hours, and 168 hours) at -60°C in the crystallization step S2. The storage time "0 hours" is the result of storing the vulcanized rubber stored at room temperature in a device set to -30°C for 15 minutes and then measuring at -30°C. Similarly, the vulcanized rubber stored at -60°C was stored in a device set to -30°C for 15 minutes and then measured at -30°C.

[0051] As shown in Figures 2 and 3, ΔT2 (1) ,ΔT2 (2)In both cases, it was possible to distinguish the properties of compositions 1, 2, and 3. As the storage time at -60°C increased, composition 3 showed a longer transverse relaxation time (T2 (1) ,T2 (2) ) is shorter, it can be said that the amount of rigid components is increasing, that is, low-temperature crystallinity is developing. It can be determined that composition 3 has relatively poor low-temperature properties compared to composition 1 and composition 2. For composition 3, a change in the transverse relaxation time was already observed after 24 hours of storage at -60°C, but there was almost no change between 72 hours and 168 hours. From this, it can be said that a storage time of 24 hours or more at -60°C is preferable, and 72 hours is sufficient.

[0052] T2 in the first measurement step (1) ,T2 (2) and T2 in the second measurement step (1) ,T2 (2) is the transverse relaxation time (T2), and each is substituted into the above equation (1) to obtain the rate of change (ΔT2 (1) ,ΔT2 (2) The measurement was performed twice, and the reproducibility was confirmed. The rate of change (ΔT2 (1) ,ΔT2 (2) ) (%) are shown in Table 2.

[0053] [Table 2]

[0054] The rate of change in the transverse relaxation time of the less mobile component (ΔT (1) ) is 10% or more, and the rate of change in the transverse relaxation time of the highly mobile component (ΔT2 (2) ) was judged to have poor low-temperature properties when it decreased by 20% or more. As shown in Table 2, a significant difference was confirmed between Compositions 1 and 2 and Composition 3 when stored at -60°C for 24 hours.

[0055] [Dynamic spring test results] A dynamic spring test was carried out at -30°C on vulcanized rubber exposed to the same specified temperature (Tc) and storage time as in Example 1, and the results were compared with the results of Example 1 according to the technology of the present disclosure.

[0056] Specifically, vulcanized rubber cut into a cylindrical test shape with a diameter of 30 mm and a thickness of 30 mm was stored at a specified temperature (Tc) for a specified time to promote crystallization. The vulcanized rubber was then subjected to a test at the specified temperature (Tc) using a dynamic property tester (KCH701, manufactured by Saginomiya Seisakusho) in which a constant displacement harmonic compression vibration with a frequency of 20 Hz and an amplitude of ±0.1 mm was applied, and the dynamic spring constant (Kd1) at 20 Hz was calculated in accordance with JIS K6385. Separately, similar measurements were also performed at room temperature without crystallization, and the dynamic spring constant (Kd2) was calculated. Then, using the following equation (Kd1-Kd2) / Kd2 x 100 The value derived from was taken as the rate of change and used as an evaluation index showing low-temperature crystallinity. From the rate of change in dynamic spring constant, it was found that composition 3 had higher low-temperature crystallinity than compositions 1 and 2. This result was highly correlated with the evaluation result based on the rate of change ΔT2 calculated in Example 1 of the technology disclosed herein. This confirmed that the rate of change in transverse relaxation time (T2) obtained by pulse NMR measurement can be used as an index for low-temperature crystallinity evaluation and is highly reliable.

[0057] [Comparative Example 1] The transverse relaxation time (T2) of the vulcanized rubbers of compositions 1 to 3 stored at room temperature was measured in the first measurement step. In addition, the transverse relaxation time (T2) of each vulcanized rubber was measured in the second measurement step after storing it at -60°C for 0 hours, 24 hours, 48 ​​hours, and 72 hours. The conditions were the same as in Example 1, except that the measurement temperature of the pulse NMR was -20°C.

[0058] The transverse relaxation time (T (1) ,T2 (2)4 and 5 are graphs in which the value of the temperature difference is plotted against the storage time (0 hours, 24 hours, 48 ​​hours, and 72 hours) at -60°C in the crystallization step S2. The storage time "0 hours" is the result of storing the vulcanized rubber stored at room temperature in a device set to -20°C for 15 minutes and then measuring at -20°C. Similarly, the vulcanized rubber stored at -60°C was stored in a device set to -20°C for 15 minutes and then measured at -20°C.

[0059] As shown in FIG. 4 and FIG. 5, when pulse NMR measurements were performed at −20° C., almost no change in the transverse relaxation time was observed for compositions 1 to 3 due to low-temperature storage.

[0060] In addition, T2 in the first measurement step (1) ,T2 (2) and T2 in the second measurement step (1) ,T2 (2) is the transverse relaxation time (T2), and each is substituted into the above equation (1) to obtain the rate of change (ΔT2 (1) ,ΔT2 (2) ) was calculated. The rate of change for each storage time (ΔT2 (1) ,ΔT2 (2) ) (%) are shown in Table 3.

[0061] [Table 3]

[0062] As shown in Table 3, when pulsed NMR measurements were performed at -20°C, the rate of change in transverse relaxation time (ΔT2 (1) ,ΔT2 (2) ) was less than 10%, and no significant difference was observed among compositions 1 to 3.

[0063] It is speculated that the low-temperature crystallization phenomenon was not observed at -20°C due to the high mobility of rubber (the effect of cross-linking). From this result, it can be said that evaluation by pulse NMR measurement at -20°C is not an appropriate evaluation condition.

[0064] [Comparative Example 2] The transverse relaxation time (T2) of the vulcanized rubbers of compositions 1 to 3 stored at room temperature was measured in the first measurement step. In addition, the transverse relaxation time (T2) of each vulcanized rubber was measured in the second measurement step after storing it at -60°C for 0 hours and 168 hours. The conditions were the same as those in Example 1, except that the measurement temperature of the pulse NMR was -60°C.

[0065] The transverse relaxation time (T (1) ,T2 (2) 6 and 7 are graphs plotting the α-methyl-2-pyrrolidone (α-methyl-2-pyrrolidone) versus storage times of 0 hours and 168 hours at -60°C in the crystallization step S2. The storage time "0 hours" is the result of storing vulcanized rubber stored at room temperature in a device set to -60°C for 15 minutes and then measuring at -60°C. The vulcanized rubber stored at -60°C was also stored in a device set to -60°C for 15 minutes and then measured at -60°C.

[0066] As shown in FIG. 6 and FIG. 7, when pulse NMR measurements were performed at −60° C., almost no change in the transverse relaxation time was observed for compositions 1 to 3 due to low-temperature storage.

[0067] In addition, T2 in the first measurement step (1) ,T2 (2) and T2 in the second measurement step (1) ,T2 (2) is the transverse relaxation time (T2), and each is substituted into the above equation (1) to obtain the rate of change (ΔT2 (1) ,ΔT2 (2) ) was calculated. The rate of change for each storage time (ΔT2 (1) ,ΔT2 (2) ) (%) are shown in Table 4.

[0068] [Table 4]

[0069] As shown in Table 4, when pulsed NMR measurements were performed at -60°C, the rate of change in transverse relaxation time (ΔT2 (1) ,ΔT2(2) ) was less than 10%, and no significant difference was observed among compositions 1 to 3.

[0070] At -60°C, the rubber is not moving, so it is assumed that the effect of crystallization is not captured. From this result, it can be said that evaluation by pulse NMR measurement at -60°C is not an appropriate evaluation condition.

[0071] [Comparative Example 3] In Comparative Example 3, an attempt was made to evaluate low-temperature crystallinity by pulse NMR measurement using the spin echo method. The spin echo method is a method for evaluating substances with large mobility.

[0072] The transverse relaxation time (T2) of the vulcanized rubbers of compositions 1 to 3 stored at room temperature was measured in the first measurement step. In addition, the transverse relaxation time (T2) of each vulcanized rubber was measured in the second measurement step after storing it at -60°C for 0 hours and 168 hours. The pulse NMR measurement device and measurement conditions are as follows. Equipment: Bruker, mq20 Sample volume: approx. 0.3 mL Observation kernel: 1 H Pulse sequence: Spin echo method Measurement temperature: 0℃ First Duration: 0.01ms Final Pulse Separation: 10 ms Data point fitting:40 Scans:16 FIG. 8 is a graph plotting the transverse relaxation time (T2) obtained in the second measurement step against the storage time (0 hours, 168 hours) at -60°C in the crystallization step S2. The storage time "0 hours" is the result of storing the vulcanized rubber stored at room temperature in a device set to 0°C for 15 minutes and measuring at 0°C. Similarly, the vulcanized rubber stored at -60°C was stored in a device set to 0°C for 15 minutes and then measured at 0°C.

[0073] As shown in FIG. 8, when pulsed NMR measurements were performed at 0° C. by the spin echo method, almost no change in the transverse relaxation time was observed for compositions 1 to 3 due to low-temperature storage.

[0074] In addition, the rate of change (ΔT2) was calculated by applying the T2 in the first measurement step and the T2 in the second measurement step to the above formula (1). The rate of change (ΔT2) (%) for each storage time is shown in Table 5.

[0075] [Table 5]

[0076] As shown in Table 5, when pulse NMR measurements were performed at 0°C using the spin echo method, even when the low-temperature storage time was extended to 168 hours, the rate of change in transverse relaxation time (ΔT) was less than 10% in all cases, and no significant difference was observed between compositions 1 to 3.

[0077] At 0°C, the rubber has a high degree of mobility (the effect of cross-linking), so it is assumed that the phenomenon of low-temperature crystallization is not captured by the spin echo method at 0°C. From this result, it can be said that evaluation by pulse NMR measurement using the spin echo method is not an appropriate evaluation condition.

Claims

1. A method for evaluating low-temperature crystallinity of vulcanized rubber using pulsed NMR, comprising the steps of: A first measurement step of deriving the mobility of the vulcanized rubber in a non-crystallized molten state from the transverse relaxation time (T2) measured using a solid echo method of pulsed NMR; a crystallization step of cooling the vulcanized rubber to a predetermined temperature (Tc) at which the vulcanized rubber can be crystallized and storing the vulcanized rubber at the predetermined temperature (Tc) for a certain period of time to promote crystallization of the vulcanized rubber; a second measuring step of deriving the mobility of the vulcanized rubber crystallized in the crystallization step from a transverse relaxation time (T2) measured by a solid echo method of pulsed NMR; a step of calculating a rate of change (ΔT2) in the transverse relaxation time from the measured transverse relaxation time (T2) in the first measurement step and the measured transverse relaxation time (T2) in the second measurement step by the following formula (1), and evaluating the crystallinity of the vulcanized rubber using the rate of change (ΔT2) as an evaluation index. {(transverse relaxation time (T2) in the second measurement step / transverse relaxation time (T2) in the first measurement step)-1} x 100 ... formula (1)

2. 2. The method for evaluating low-temperature crystallization of vulcanized rubber according to claim 1, wherein the vulcanized rubber contains natural rubber or isoprene rubber.

3. 3. The method for evaluating low-temperature crystallinity of vulcanized rubber according to claim 2, wherein the predetermined temperature (Tc) is a temperature 10° C. to 40° C. higher than the glass transition temperature (Tg) of natural rubber or isoprene rubber.

4. 4. The method for evaluating low-temperature crystallization of vulcanized rubber according to claim 3, wherein the predetermined temperature (Tc) is −60° C. to −30° C.

5. 5. The method for evaluating low-temperature crystallinity of vulcanized rubber according to claim 3, wherein the pulse NMR measurements in the first measurement step and the second measurement step are performed at a temperature higher than -60°C and lower than -20°C.

6. The method for evaluating low-temperature crystallization of vulcanized rubber according to any one of claims 1 to 5, wherein the certain period of time is at least 24 hours.

Citation Information

Patent Citations

  • Semi-finished contact lens having completely formed back geometry, manufacture thereof and manufacture of contact lens

    JP1986041118A

  • Method for estimating durable life of rubber belt

    JP2001249091A

  • Method for measuring crystallinity

    JP2013205084A

  • Rubber masterbatch and method for producing the same

    JP2020066700A

  • Rubber inspection method

    JP2020085777A